Pedro de Rivera and the Military Regulations for Northern New Spain, 1724-1729 (University of Arizona Press, 1989)
Philip V ordered an inspection of the presidios in the northern provinces which resulted in the reglamento of 1729. The study was capably done and documented by Pedro de Rivera Villalon. Includes Rivera’s report to the Viceroy of New Spain, the Reglamento of Havana , the inspection, Alvarez Barreiro’s map and descriptions. The documents are presented in their original Spanish and in translation, provide a detailed background by which modern scholars can better assess the status and role of Spain's military outposts